CHILDFREE MENURUT FATWA DAR AL-IFTA’ JORDAN DAN LEMBAGA BAHTSUL MASAIL PCINU MESIR DALAM MAQASID SYARIAH - Syarifatus Shalihah Khairati; Muchlis Bahar; Zulfan Zulfan (Kampus Akademik Publiser, 2024)
Abstract. This research examines childfree according to the fatwa of Dar Al-Ifta' Jordan and the Egyptian PCINU Bahtsul Masail Institute in maqasid sharia. Childfree is an agreement between husband and wife not to have children in marriage. Using a normative analysis approach, it can be seen that childfree in the view of the Dar Al-Ifta' Jordan Egypt fatwa which is reviewed by maqasid sharia is closer to the value of maqasid sharia, while the Egyptian LBM PCINU allows the practice of childfree by analogizing it with 'azl, whereas the permissibility of 'azl is only temporary, not to be permanent, then here LBM PCINU Egypt's decision regarding childfree is not in line with maqasid sharia values. Because Childfree's decision is contrary to the purpose of marriage in Islam, namely to continue the offspring and human population, as in the words of the QS. An-Nahl:72 and Hadith Abu Dawud 2050.